2011
DOI: 10.1016/j.jval.2011.08.848
|View full text |Cite
|
Sign up to set email alerts
|

PCV128 A Real World Evaluation to Describe the Characteristics, Outcomes and Resource Use Associated with Patients Being Managed by a Secondary Care Based Anticoagulation Service

Abstract: with relevant follow up for positive tests. Prior to the test, attenders were given a questionnaire about their doubt and arguments in relation to the participation decision, including different willingness-to-pay (WTP) questions. Non-attenders were mailed a similar questionnaire. RESULTS: 70% responded to the questionnaire, which lead to a study sample of 1,053 attenders and 435 non-attenders. Among attenders, 5% had doubt about participation and the most frequent argument was that they did not want to know a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A particularly critical area of uncertainty identified a priori during model development was INR monitoring frequency. Owing to wide variation in both UK clinical practice and published estimates [ 15 , 16 , 18 , 56 ], a service evaluation and national survey were conducted to obtain the models of anticoagulation, quantify its distribution and collect resource-use data to ensure that the analysis represented clinical practice [ 51 ]. Local care pathways will determine whether such savings can be realized consistently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A particularly critical area of uncertainty identified a priori during model development was INR monitoring frequency. Owing to wide variation in both UK clinical practice and published estimates [ 15 , 16 , 18 , 56 ], a service evaluation and national survey were conducted to obtain the models of anticoagulation, quantify its distribution and collect resource-use data to ensure that the analysis represented clinical practice [ 51 ]. Local care pathways will determine whether such savings can be realized consistently.…”
Section: Discussionmentioning
confidence: 99%
“…Because warfarin is the most commonly used VKA for VTE treatment in the UK [ 12 ], and was also the most frequently used VKA in the EINSTEIN DVT and EINSTEIN PE studies [ 25 , 26 ], it was selected for the model. To facilitate understanding of the contemporary provision of anticoagulation care, a survey of models of care was conducted (Bayer, data on file) [ 51 ]. Results suggested that, instead of traditional secondary care (consultant-led services), primary care is now the most common setting for provision of these services.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…greater than 2), a negative D-dimer test result and a positive ultrasound result then treatment commences (7.728% of all cases -see Outcome 2 from Table 2). Note that there are many combinations and the percentages are calculated using the values shown in Typically, 22%, 63% and 15% of provoked patients on Warfarin visit anticoagulation clinics (also known as INR clinics) on an average of 9, 14 and 24 times over 3, 6 and 12 months, respectively (Winter, Keeling , Sharpen, Cohen, & Vallance, 2005) (Rose, James, Chapman, & Marshall, 2011). In the case of Unprovoked patients on Warfarin, 6%, 63% and 31% visit INR clinics on average of 9, 14 and 24 times over 3, 6 and 12 months, respectively.…”
Section: Additional Setting Descriptionmentioning
confidence: 99%